ZnO decorated luminescent graphene as a potential gas sensor at room temperature - Choudhary, Anshul (Elsevier, 2012)
We present a simplistic single step synthesis and a detailed study of the remarkable room temperature gas sensing and photoluminescence (PL) properties of zinc oxide (ZnO) decorated graphene oxide sheets (GrO). Investigation of opto-electronic properties reveal near UV to blue PL and semiconducting behavior of ZnO–GrO sheets. ZnO nano-crystallites serve the dual purpose of acting as a nano-spacer between dried graphene sheets as well as a primary sensing transducer for the gas sensing applications. PL has been used as a tool to study the defects associated with the surface of the nanocrystallite’s trap levels and/or acceptor–donor recombinations. Time-resolved PL was used to determine free carrier or exciton lifetimes, a vital parameter related to quality of composite and device performance. Results are presented for the detection of common industrial toxins like CO, NH3 and NO for concentrations as low as 1 ppm at room temperature. A large sensor response and quick recovery time was observed at room temperature with preferred selectivity towards electron donor gases like CO and NH3.
Only IISERM authors are available in the record.
Keywords: Synthesis; Room temperature; Nano-spacer